Efektivitas Model Mind Mapping Berbasis Kontekstual Pada Pebelajaran IPA Sekolah Dasar - Yulmianthi Pongnupa'; Jusmawati; Cayati; Satriawati (Kappa Journal, 2024)
This research was conducted to determine the comparison of the effectiveness of the contextual-based mind mapping model for fifth grade science learning at SD Inpres Hombes Armed, Gowa Regency. This research aims to determine the effectiveness of using a contextual-based mind mapping model for class V science learning at SD Inpres Hombes Armed. This research uses a pre-experimental quantitative approach with a one group pretest posttest research design with a VA class sample of 30 students. The research instruments used were teacher activity observation sheets, student activity observation sheets, learning results tests and questionnaires, as well as data collection techniques carried out by observation, tests and questionnaires which were reviewed based on student activities, results and responses. After analyzing the data, the researcher obtained an average value of teacher activity of 3.6 which was in the very good category, an average value of student activity of 3.4 in the good category, an average value of learning outcomes of 3.4 in the good category and an average value of -The average student response was 3.6 in the very good category. So, through the results of data analysis, it can be concluded that the contextual-based mind mapping model in science learning is effectively used, indicated by the score obtained at 3.3 in the quite effective category.